2019
DOI: 10.1109/access.2019.2939019
|View full text |Cite
|
Sign up to set email alerts
|

Norm-Based Behavior Regulating Technique for Multi-Agent in Complex Adaptive Systems

Abstract: In a complex adaptive system, norms are widely used to regulate agents' behavior within a society in which the agents are not explicitly given the norms of different host systems, but instead detect and adapt the norms autonomously. Thus, failing to adopt a host's norms resulting in deprived of accessing resources and services that would severely affect their performance. Few attempts have been made to overcome this problem but proposed solutions lack accuracy in identifying the norms of a domain. Consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To identify environmental norms, [43] proposes the RNDT (Regulative Norms Detection Technique), a technique to detect norms considering their rewards and penalties. Even though addressing norms challenges is not our focus, the authors proposed a norm taxonomy that classifies norms as follows: (i) regulative, (ii) constructive, and (iii) procedural.…”
Section: B Multiagent Systemsmentioning
confidence: 99%
“…To identify environmental norms, [43] proposes the RNDT (Regulative Norms Detection Technique), a technique to detect norms considering their rewards and penalties. Even though addressing norms challenges is not our focus, the authors proposed a norm taxonomy that classifies norms as follows: (i) regulative, (ii) constructive, and (iii) procedural.…”
Section: B Multiagent Systemsmentioning
confidence: 99%
“…It was shown that in the pattern mining of multi-agent networks, relying on occurrence frequency is sometimes misleading and new metrics such as sequence virtual growth rate are necessary to identify highly correlated patterns with a significant trend sequence in the graph [166]. Norm mining is another category that investigates events triggering rewards and penalties and identifies the norms in a varying environment setting [167]. This will help agents to survive and adapt to their environment without the deprivation of their resources and services.…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…Agent technology is widely used in grid systems [13] [14]. An agent can sense the environment, take appropriate actions to establish its own code of conduct and influence environmental change, which provides an effective tool for solving network distributed application problems [15] [16] [17]. Thus, agent technology is introduced for improving the scalability, stability and efficiency of grid systems in this model.…”
Section: A Agent-based Grid Structurementioning
confidence: 99%